Mean Oxygen Saturation during Sleep Is Related to Specific Brain Atrophy Pattern. Issue 6 (20th April 2020) - Marchi, Nicola Andrea; Ramponi, Cristina; Hirotsu, Camila; Haba‐Rubio, José; Lutti, Antoine; Preisig, Martin; Marques‐Vidal, Pedro; Vollenweider, Peter; Kherif, Ferath; Heinzer, Raphael; Draganski, Bogdan
Abstract : Objective: There is much controversy about the neurobiological mechanisms underlying the effects of sleep‐disordered breathing on the brain. The aim of this study was to investigate the association between markers of sleep‐related hypoxemia and brain anatomy. Methods: We used data from a large‐scale cohort from the general population (n = 775, 50.6% males, age range = 45–86 years, mean age = 60.3 ± 9.9) that underwent full polysomnography and brain magnetic resonance imaging to correlate respiratory variables with regional brain volume estimates. Results: After adjusting for age, gender, and cardiovascular risk factors, only mean oxygen saturation during sleep was associated with bilateral volume of hippocampus (right: p = 0.001; left: p < 0.001), thalamus (right: p < 0.001; left: p < 0.001), putamen (right: p = 0.001; left: p = 0.001), and angular gyrus (right: p = 0.011; left: p = 0.001). We observed the same relationship in left hemispheric amygdala ( p = 0.010), caudate ( p = 0.008), inferior frontal gyrus ( p = 0.004), and supramarginal gyrus ( p = 0.003). The other respiratory variables—lowest oxygen saturation, percentage of sleep time with oxygen saturation < 90%, apnea–hypopnea index, and oxygen desaturation index—did not show any significant association with brain volumes. Interpretation: Lower mean oxygen saturation during sleep was associated with atrophy of cortical and subcortical brain areas known for high sensitivity to oxygen supply. Their vulnerability to hypoxemia may contribute to behavioral phenotype and cognitive decline in patients with sleep‐disordered breathing. ANN NEUROL 2020;87:921–930